2019
DOI: 10.1186/s12864-019-6094-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and their regulatory networks in Chinese Gushi chicken abdominal adipose tissue during postnatal late development

Abstract: BackgroundAbdominal fat is the major adipose tissue in chickens. The growth status of abdominal fat during postnatal late development ultimately affects meat yield and quality in chickens. MicroRNAs (miRNAs) are endogenous small noncoding RNAs that regulate gene expression at the post-transcriptional level. Studies have shown that miRNAs play an important role in the biological processes involved in adipose tissue development. However, few studies have investigated miRNA expression profiles and their interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 91 publications
(95 reference statements)
2
37
0
Order By: Relevance
“…In chicken, the first products of de novo fatty acid synthesis are SFAs, including palmitic acid (C16:0) [ 26 ], which then genes, such as ELOVL6, can catalyze the elongation of palmitic acid (C16:0) to create stearic acid (C18:0). Subsequently, through initial desaturation of saturated fatty acids to monounsaturated fatty acids, SCD catalyzes the desaturation of palmitic and stearic acid to palmitoleic acid (C16:1) and oleic acid (C18:1), respectively [ 6 , 27 ]. Further fatty acids elongation and desaturation are catalyzed via enzymes encoded by ELOVLs, as well as FADS1 and FADS2 [ 15 ] ( Figure 1 ), which ELOVLs are essential for the rate-limiting step in the elongation cycle during the synthesis of long- and very-long-chain fatty acids (LCFA, VLCFA) [ 23 ].…”
Section: Overview Of Lipid Metabolism In Chickenmentioning
confidence: 99%
See 1 more Smart Citation
“…In chicken, the first products of de novo fatty acid synthesis are SFAs, including palmitic acid (C16:0) [ 26 ], which then genes, such as ELOVL6, can catalyze the elongation of palmitic acid (C16:0) to create stearic acid (C18:0). Subsequently, through initial desaturation of saturated fatty acids to monounsaturated fatty acids, SCD catalyzes the desaturation of palmitic and stearic acid to palmitoleic acid (C16:1) and oleic acid (C18:1), respectively [ 6 , 27 ]. Further fatty acids elongation and desaturation are catalyzed via enzymes encoded by ELOVLs, as well as FADS1 and FADS2 [ 15 ] ( Figure 1 ), which ELOVLs are essential for the rate-limiting step in the elongation cycle during the synthesis of long- and very-long-chain fatty acids (LCFA, VLCFA) [ 23 ].…”
Section: Overview Of Lipid Metabolism In Chickenmentioning
confidence: 99%
“…There are several genes involving in different stages of fat metabolism in chicken, which their expression is regulated via different miRNAs [ 27 ], transcription factors [ 11 ], and hormones [ 30 ]. Some of these genes, including ACACA, FASN, SCD, ELOVL6, and ACLY, encoding major enzymes catalyzing important steps in different lipid-related processes in chicken.…”
Section: Important Genes Involved In Chicken Fat Metabolismmentioning
confidence: 99%
“…cDNAs from mRNA were synthesized using a RevertAid First Strand cDNA Synthesis kit (Thermo Scientific, Waltham, MA, USA). In brief, the reaction mixture (20 μL) contained RNA (2 μg), 5× Reaction Buffer (4 μL), 10 mM dNTP Mix (2 μL), Oligo (dT) 18 primers (1 μL), RiboLock RNase Inhibitor (1 U), and RevertAid M-MuLV RT (10 U). The reaction was subjected to the following conditions: 60 min at 42 °C, followed by 70 °C for 5 min.…”
Section: Quantitative Real-time Pcr (Qrt-pcr) For Mrna and Mirnamentioning
confidence: 99%
“…In chicken, gga-miR-200a regulated cell differentiation and proliferation of breast muscle by target 3′-UTR of GRB2 [17]. Additionally, gga-miR-200-3p was expressed in high abundance between 14 weeks and 22 weeks, and it also targeted TGFB3 related to TGFbeta signaling pathway and MAPK signaling pathway in abdominal adipose tissue during postnasal late development [18]. In response against Reticuloendotheliosis Virus, gga-miR-200a-3p was negatively correlated with CTLA4, a negative regulator of T cell activation in spleen [19].…”
Section: Introductionmentioning
confidence: 99%
“…Integration of these profiles with RNA-seq data indicated that these differentially expressed miRNA target genes were associated with adipocyte differentiation and lipid disposition ( Huang et al., 2015 ). MicroRNA profiling of abdominal adipose tissue of Gushi (Chinese domestic breed) hens found the expression of 16 miRNA decreased and 12 miRNA increased from 6 wk to 30 wk of age and these miRNA target genes were associated with adipocyte development, lipid metabolism, and cell junctions ( Chen et al., 2019b ). Differentiation (in vitro) of primary chicken preadipocytes, obtained from abdominal adipose tissue of 14-day-old Gushi chickens, altered the expression of 80 miRNA, 58 upregulated and 22 downregulated ( Ma et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%